Nutritional Evaluation of a Dehydrated Shredded Meat Product, (Danbunama) - Ogunsola, O.O.; Omojola, A.B. (Pakistan Journal of Nutrition, 2008)
The qualitative effects of different oil types used in processing of danbunama, a dehydrated shredded meat product in relation to its palatability, physical, chemical and nutritional attributes are the focus of this study. The effect of different oil types on the sensory qualities of the product was carried out using semitendinosus part of beef. The three different oil types used, decolorized palm oleic oil (T1) local bleached palm oil (T2) and pure groundnut-oil (T3) were subjected to lipid oxidation analysis to determine the Thiobarbituric acid value (TBA) peroxide and acid values at 1st, 3rd, 6th and 9th weeks of storage. Sensory evaluation showed that there were no significant differences amongst the oil types used on the parameters tested for. The proximate analysis of danbunama determined showed its moisture range to be 4.22-4.50%, crude protein% range of 38.9-43.5%, T1 differed significantly from that of T2 and T3, the crude fat% differed significantly for all oil types. Lipid oxidation in T3 (0.70±0.01) was significantly higher at week 6 while T1 (0.81±0.01) recorded a significantly higher value at week 9. Danbunama can be prepared from any of the oil types and with proper packaging, the nutritional status of the product at week 1 does not significantly differ from that at week 9. The product is a nutritive meal or snack, easy to carry requiring no sophisticated packaging and is quite stable at room temperature. Rancidity will not pose a treat if good quality raw materials are utilized during processing.